Entrepreneurial learning: a bibliometric analysis of the past decade (Research, Society and Development, 2022)
The present bibliometric study aims to analyze the scientific production on the theme Entrepreneurial Learning, in the Web of Science (WoS) and Scopus (Capes, 2020) databases. This research is characterized with a descriptive nature, quantitative approach and application of bibliometric analysis. Using the theme "entrepreneurial learning", the search was delimited in the period from 2010 to 2020. The analysis considered the following elements: time evolution, total number of publications, thematic area, type of document, countries, main authors and citation report. As a method for data analysis, the VOSviewer system was used to create textual maps, co-citation clusters and keywords. The results of the research show that the topic is opportune, highlighting that the type of publication with the greatest quantity is in the form of an article in the two bases surveyed. In addition, the theme has been growing gradually over the years and the publications in the Scopus database are concentrated in the United Kingdom, already in WoS, in England. It should also be noted that the area that most researches on Entrepreneurial Learning is Business, management and accounting, at Scopus and Business Economics at WoS. As a limitation of the study, the realization in only two databases stands out. It is suggested for future studies, that the sample be extended to include academic, national and international events, journals, as well as other scientific databases.